(untitled) (Tempo e Argumento, 2021)
This article analyzes the impact of Communist propaganda on Argentine repressive policies, implemented in the mid-20th century. In the general framework of the cultural diplomacy of the European Socialist countries with respect to Argentina I intend to analyze a type of propaganda aimed at a reduced public, formed by the Slavic immigrant communities, with the aim of achieving their re-displacement to Soviet territory or territories occupied by communist regimes in Eastern Europe. These repatriation campaigns implemented between 1953 and 1961 raised concerns in successive local governments about the legal status and national identity of the returnees. In response to this, the Argentine State reinforced its mechanisms of control and repression, outlining in these measures a first concept of "internal enemy."